PENERAPAN ARSITEKTUR TROPIS PADA HOTEL RESORT DIKAWASAN PANTAI POHON CINTA - Bacharudin Boekoesoe; Muh Rijal Syukri; Zuhriati Djailani (JAMBURA Journal of Architecture, 2023)
ABSTRACT. Pohuwato Regency, with a hot climate and land design located on the coast, will be designed for a resort hotel building that uses the concept of tropical architecture in order to create thermal comfort for the building. Pantai Pohon Cinta is a natural tourist attraction located in Gorontalo province, specifically Pohuwato Regency, which has the potential for tourist attraction development. According to the Spatial Plan of Pohuwato Regency in 2012-2032, Pantai Pohon Cinta is included in the natural tourism designation area, while the Regional Tourism Development Master Plan of Pohuwato District regulated Pantai Pohon Cinta to be included in the development of a tourism area with a Culinary site icon.  The number of tourists in Pohuwato Regency, which is predicted to increase, is not comparable with the provision of accommodation in the tourist area of Pohuwato Regency; therefore, Pantai Pohon Cinta Resort Hotel is designed to facilitate tourist activities such as playgrounds, culinary areas, Water Sports, Souvenir centers and lodging. Resort Hotels are defined as hotels located in the tourist area where most staying visitors are not conducting business activities. It is generally located quite far from the city center, which functions as a resting place and simultaneously provides facilities for vacation, recreation, and sports. The result of this final project is a Resort Hotel with a three-star hotel capacity which is analyzed through the calculation of visitor growth in the next 20 years.  The concept of the building's mass management used in the area of the Resort Hotel is a linear pattern in order to provide convenience to connect the existing buildings around the site, while the concept of the building mass design is based on values that contain local wisdom as characteristics of buildings from Gorontalo area.   Keywords Resort Hotel, Tropical, Beach, Tourism,  ABSTRAK. Kabupaten Pohuwato yang beriklim panas dan lahan lokasi perancangan berada di pesisir pantai maka akan dirancang bangunan hotel resort yang menggunakan konsep Arsitektur Tropis Lembab agar dapat terciptanya kenyamanan thermal bagi bangunan. Pantai Pohon Cinta merupakan objek wisata alam yang terletak di Provinsi Gorontalo khususnya Kabupaten Pohuwato, yang memiliki potensi pengembangan objek wisata. Menurut Rencana Tata Ruang Wilayah Kabupaten Pohuwato Tahun 2012-2032 Pantai Pohon Cinta masuk dalam kawasan peruntukan pariwisata alam. Dan menurut Rencana Induk Pengembangan Pariwisata Daerah Kabupaten Pohuwato, Pantai Pohon Cinta termasuk pengembangan kawasan pariwisata dengan ikon Culinerry site.  Jumlah wisatawan di Kabupaten Pohuwato yang diprediksi akan mengalami peningkatan tidak berberbanding dengan penyediaan akomodasi di Kawasan wisata Kabupaten Pohuwato maka dari itu dirancanglah Hotel Resort Pantai Pohon Cinta yang dapat memfasilitasi kegiatan wisata seperti taman bermain, area kuliner, olahraga air, pusat cinderamata serta penginapan. Hotel Resort didefinisikan sebagai hotel yang terletak dikawasan wisata, dimana sebagian pengunjung yang menginap tidak melakukan kegiatan usaha. Umumnya terletak cukup jauh dari pusat kota sekaligus difungsikan sebagai tempat peristirahatan dan menyediakan fasilitas untuk berlibur, rekreasi dan olah raga. Hasil dari tugas akhir ini berupa Hotel Resort dengan kapasitas hotel bintang tiga yang dianalisis melalui perhitungan pertumbuhan pengunjung 20 tahun yang akan datang. Konsep tata masa bangunan yang digunakan pada kawasan Hotel Resort Pantai Pohon Cinta adalah pola linear, agar dapat memberikan kemudahan untuk menghubungakan bangunan yang ada di sekitaran site sedangan konsep rancangan masa bangunan Hotel Resort Pantai Pohon Cinta didasarkan pada nilai-nilai yang mengandung kearifan lokal sebagai ciri khas bangunan dari daerah Gorontalo.  Kata kunci: Hotel Resort, Tropis, Pantai, Pariwisata